(untitled) (Baghdad Science Journal, 2009)
The effect of using different R -molar ratio under variable reaction conditions (acidic as well as basic environment and reaction temperature) have been studied. The overall experiments are driven with open and closed systems. The study shows that there is an optimum value for a minimum gelling time at R equal 2. The gelling time for all studied open system found to be shorter than in closed system. In acidic environment and when R value increased from 2 to 10, the gelling time of closed systems has increased four times than open systems at T=30 ?C and fourteen times when temperature reaction increased to 60 ?C. While in basic environment the influence of increasing R value was limited.